A protein coupling and molecular simulation analysis of the clinical mutants of androgen receptor revealed a higher binding for Leupaxin, to increase the prostate cancer invasion and motility. (July 2022) - Khan, Abbas; Li, Wenfeng; Ambreen, Amna; Wei, Dong-Qing; Wang, Yanjing; Mao, Yuanshen
Abstract: Recently a novel coactivator, Leupaxin (LPXN), has been reported to interact with Androgen receptor (AR) and play a significant role in the invasion and progression of prostate cancer. The interaction between AR and LPXN occurs in a ligand-dependent manner and has been reported that the LIM domain in the Leupaxin interacts with the LDB (ligand-binding domain) domain AR. However, no detailed study is available on how the LPXN interacts with AR and increases the (prostate cancer) PCa progression. Considering the importance of the novel co-activator, LPXN, the current study also uses state-of-the-art methods to provide atomic-level insights into the binding of AR and LPXN and the impact of the most frequent clinical mutations H874Y, T877A, and T877S on the binding and function of LPXN. Protein coupling analysis revealed that the three mutants favour the robust binding of LPXN than the wild type by altering the hydrogen bonding network. Further understanding of the binding variations was explored through dissociation constant prediction which demonstrated similar reports as the docking results. A molecular simulation approaches further revealed the dynamic features which reported variations in the dynamics stability, protein packing, hydrogen bonding network, and residues flexibility index. Furthermore, we also assessed the protein motion and free energy landscape which also demonstrated variations in the internal dynamics. The binding free energy calculation revealed -32.95 ± 0.17 kcal/mol for the wild type, for H874Y the total binding energy (BFE) was -36.69 ± 0.11 kcal/mol, for T877A the BFE was calculated to be -38.78 ± 0.17 kcal/mol while for T877S the BFE -41.16 ± 0.12 kcal/mol. This shows that the binding of LPXN is increased by these mutations which consequently increase the PCa invasion and motility. In conclusion, the current study helps in understanding the protein networks and particular the coupling of AR-LPXN in prostate cancer and is of great interest in deciphering the molecular mechanism of disease and therapeutics developments. Highlights: Leupaxin (LPXN) interact with Androgen receptor (AR) and play a significant role in the invasion and progression of PCa. However, no detailed study is available on how the LPXN interacts with AR and increases the prostate cancer progression. The current study also uses state-of-the-art methods to provide atomic-level insights into the binding of AR and LPXN. Protein coupling analysis revealed that the three mutants favour the robust binding of LPXN than the wild type. AR-LPXN in prostate cancer is important to decipher the molecular mechanism of disease and therapeutics developments.